Revitalisasi Asbāb Al-Wurūd Dalam Kontekstualisasi Makna Hadis: Analisis Hadis Tentang Amalan Paling Utama Riwayat Shahih Muslim - Alfia Ulul Mardliyah (Canonia Religia, 2026)
This study critically re-examines the hadith on “the most virtuous deed” narrated by ‘Abdullah bin Mas‘ud in  Ṣahīh Muslim by reconstructing the methodological function of asbāb al-wurūd. Previous studies generally treated asbāb al-wurūd either as descriptive historical background or as a thematic interpretive tool without integrating systematic takhrīj and sanad–matn criticism. This article differs by establishing contextual interpretation only after verifying the authenticity of the transmission through comprehensive takhrīj across  Ṣahīh al-Bukhari,  Ṣahīh Muslim, and Musnad Ahmad. Using library research and thematic-contextual analysis, the study demonstrates three main findings. First, the hadith qualifies as ṣaḥīḥ li-dhātih based on uninterrupted chains of transmission, reliable transmitters, and the absence of shādh and hidden defects. Second, lexical variations such as afḍal versus aḥabb ilā Allāh and li-waqtihā versus ‘alā waqtihā constitute tanawwu‘ lafẓī that do not alter normative meaning. Third, the identified asbāb al-wurūd represents a verified micro-context embedded within the dialogical structure of the narration, indicating that the hierarchy of deeds was historically responsive rather than a rigid universal ranking. Theoretically, this study proposes an integrative model in which asbāb al-wurūd functions as a transmission-based hermeneutical instrument. This model bridges classical ḥadīth criticism and contextual interpretation, offering a structured epistemological framework for contemporary hadith studies.